Negative correlation between retirement age and contribution length? - Erik Granseth; Wolfgang Keck; Wolfgang Nagl; András Simonovits; Melinda Tir (Hungarian Academy of Sciences, Institute of Economics, 2016)
Though never stated explicitly, there is a hidden hypothesis that in a normal pension system, the retirement age and the contribution length are strongly and positively correlated. We compare the time paths of male and female correlation coefficients in Austria, Hungary, Germany and Sweden for several years and categories; and obtain a mixed picture. Hungary stands out with its strong negative correlation but the remaining three countries cannot boast with strongly positive correlation, either. Further work is needed to understand the significance of our findings but they signal some problems with these systems: heterogeneously fragmented careers and unfair benefit rules.
Keywords: H55; J26; J64; 330; public pension system; length of employment; fragmented careers; retirement age